NOTCH1 mutation and its prognostic significance in Chinese chronic lymphocytic leukemia: a retrospective study of 317 cases. (23rd March 2018) - Zou, Yixin; Fan, Lei; Xia, Yi; Miao, Yi; Wu, Wei; Cao, Lei; Wu, Jiazhu; Zhu, Huayuan; Qiao, Chun; Wang, Li; Xu, Wei; Li, Jianyong
Abstract: The proto‐oncogene NOTCH1 is frequently mutated in around 10% of patients with chronic lymphocytic leukemia (CLL). This study analyzed NOTCH1 mutation status of 317 Chinese patients with CLL by Sanger sequencing. The frequencies of NOTCH1 mutation in the PEST (proline (P), glutamic acid (E), serine (S), threonine (T)‐rich protein sequence) domain and the 3′ untranslated regions (UTR) were 8.2% and 0.9%, with the most frequent mutation being c.7541_7542delCT and c.*371A>G, respectively. Clinical and biological associations were determined including NOTCH1 mutations with advanced stage (Binet stage, P  = 0.010), unmutated immunoglobulin heavy‐chain variable region ( IGHV ) gene ( P  < 0.001) and trisomy 12 (+12) ( P  = 0.014). NOTCH1‐ mutated patients had lower CD20 expression intensity than NOTCH1‐ unmutated patients ( P  = 0.029). In addition, NOTCH1 ‐mutated patients had shorter overall survival (OS) ( P  = 0.002) and treatment‐free survival (TFS) ( P  = 0.002) than NOTCH1 ‐unmutated patients, especially for patients with NOTCH1 c.7541_7542delCT and/or c.*371A>G mutations. Patients with both mutated NOTCH1 and unmutated IGHV had shorter OS ( P  < 0.001) and TFS ( P  < 0.001) than those with unmutated NOTCH1 or mutated IGHV . These data provide a comprehensive view of the clinical relevance and prognostic impact of NOTCH1 mutations on Chinese patients with CLL. Abstract : We investigated the incidence and prognostic value of NOTCH1 mutation in 317 Chinese patients with CLL. We analyzed the clinical and molecular features of NOTCH1 mutations and highlighted different features of NOTCH1 mutations between different ethnic groups.